Outcomes of the Low Emission Food Systems Initiative in Colombia: Outcome trajectory evaluation - Camilo, Karen; Reyes, Byron (2024)
The Low Emission Food Systems Initiative (Mitigate+) focuses on three main aspects: reducing food systems (FS) emissions and the predicted consequences of climate change on future generations, sustainable development, and social equity. Through its work, the initiative ensures that civil society, multilateral, government, academic, and private sector actors in its four targeted countries (Colombia, Kenya, China, and Viet-Nam) have the knowledge, information, and tools necessary to make robust evidence-based decisions as they confront challenges in FS discourse, policy development, and implementation to reduce greenhouse gas emissions (GHGE) contributions. The Mitigate+ Initiative was designed to generate changes through three mechanisms: aligning incentives and investments, new ideas and information, and new actors and coalitions. The initiative works in five work packages. Each work package carried out diverse activities to address the main challenges encountered around reducing GHG emissions; publishing many knowledge products, implementing many workshops, and working together with diverse stakeholders to achieve its goals. This work resulted in changes in knowledge, skills, attitudes, and/or relationships (outcomes). Mitigate+’s impact assessment team had the responsibility of evaluating the contributions of the initiative to observed outcomes. This report presents the evaluation results of the outcomes identified for Colombia and uses the outcome trajectory methodology.